An analysis of the effects of the audit committees on the performance of state-owned enterprises in Zimbabwe (2011-2015). - Zimidzi, Venencia (Midlands State University, 2018)
This paper analysis the Effects of the Audit Committees on the performance of State-Owned Enterprises in Zimbabwe (2011-2015). We examine the role of the audit committee in their oversight in the performances of the SOEs. This study examines whether the quality of the audit committee, captured by its independence, expertise, and diligence, is associated with improved SOEs performance. Using a sample of internal Audit Functions of 17 SOEs out of the 78 SOEs in Zimbabwe the study found that high-quality audit committee improves oversight and hence firm performances. The study further found out that higher quality audit committee members’ skills are associated with well-coordinated internal audit work. SOEs that have a working Audit committees helps the board in an oversight and monitoring functions pertaining to the reporting and presentation of Audit work. The study recommends that the auditing skills of the auditors be improved in order to ensure appropriate articulation of issues and that internal reporting. The selection of the members to sit on the committee should be well articulated on finance and auditing functions and also that they obtain continuous capacity development.